Pengaruh Kepemimpinan Transaksional dan Reward terhadap Motivasi Ekstrinsik Karyawan pada PT Konigs Multi Teknik - Sekaria Nazara; Rosmita Rosmita (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2026)
This quantitative study examines the impact of transactional leadership and reward systems on employees' extrinsic motivation at PT Konigs Multi Teknik, addressing earlier observations of low staff motivation. Utilizing a saturated sampling technique, the research involved the entire company population of 31 employees. Data collected through five-point Likert-scale questionnaires were analyzed via multiple linear regression using SPSS version 27, successfully satisfying all required classical assumption tests The partial test (t-test) results revealed that both transactional leadership and rewards exert a positive and significant influence on extrinsic motivation, with rewards standing out as the more dominant factor. Furthermore, the simultaneous test (F-test) confirmed that both variables jointly and significantly drive employee motivation, accounting for exactly 80.9 percent of its variance according to the adjusted R-square value. Ultimately, these findings suggest that companies must strategically combine consistent transactional leadership practices with a fair, transparent reward system to effectively boost overall motivation.